Векторні моделі інформаційного пошуку - Никоненко, В. І. (My University, 2024)
The post-industrial development of society has made mathematics as the foundation for creating the most advanced technologies that would make our lives easier. In this regard, special information retrieval models have been invented. Most of them are based on mathematical knowledge, so they are considered the most convenient to use. However, there are errors in everything that only complicate the process of any activity. Some factors that cause the inefficiency of the information retrieval vector model have been studied. Problems affect the result have been analyzed. The possibilities of eliminating certain shortcomings are clarified. Prospects for further research of the model under consideration and positive aspects of the use of mathematical tools in information retrieval systems are determined.
Keywords: модель інформаційного пошуку; векторна модель